PLANT-BASED THERAPEUTIC DIETS FOR METABOLIC SYNDROME: A HOME SCIENCE INTERVENTION STUDY - Ahirwar, Sangeeta (International Journal of Research -GRANTHAALAYAH, 2025)
Metabolic syndrome (MetS) — a constellation of conditions including insulin resistance, abdominal obesity, hypertension, and dyslipidemia — represents a major global health challenge linked to poor diet and sedentary lifestyle. The increasing burden of MetS has prompted interest in plant-based therapeutic diets that target metabolic dysfunction through nutrient density, fiber content, and bioactive phytochemicals. This paper evaluates the efficacy of a plant-based dietary intervention in modulating metabolic parameters within a Home Science framework, using hypothetical yet literature-supported data. A 12-week intervention model compared three diet groups: a conventional diet, a semi-vegetarian diet, and a whole plant-based therapeutic diet emphasizing legumes, whole grains, fruits, vegetables, nuts, and minimal oil. Hypothetical data indicated that the plant-based diet group achieved substantial improvements — 22% reduction in LDL cholesterol, 18% improvement in insulin sensitivity (HOMA-IR), and 15% decrease in systolic blood pressure. The study supports the therapeutic potential of whole-food, plant-based (WFPB) diets in reversing metabolic dysregulation through mechanisms involving antioxidant activity, improved lipid metabolism, and enhanced gut microbiota function. Integrating plant-based nutrition into daily meal planning from a Home Science perspective promotes family health, disease prevention, and sustainable dietary behavior.